Caesarius of Arles: On Living in Community - DelCogliano, Mark (Cistercian studies quarterly, 2006)
The article discusses the sermon of sixth-century Gallic bishop Caesarius of Arles which emphasizes on life in a monastic community. Caesarius preached on Christian beliefs, values and practices against pagan syncretism. He described monastic vocation as conducive to the preparation of the soul for the eternal rewards promised for people and finding joy in a subordinate and humble state of life.